Vulnerability of Mass Movement Zonation Using DEM in Upstream – Midstream Kelara Watershed, Jeneponto Regency, South Sulawesi - Fathurrahman, Fathurrahman; Azikin, Busthan; Imran, A. M. (Journal of Geology and Exploration, 2024)
Mass movement is one of the major natural disasters that claim many lives and property. The Kelara watershed, which is the research area, often encounters land movements that often cause casualties. The problem of mass movement often occurs in the upstream - midstream part of the Kelara watershed with mountainous to hilly morphology with moderately steep to steeply sloping relief. The parameters used in this analysis are lithology, distance from faults, distance from rivers, distance from streets, land use, rainfall, soil type, slope, profile curvature, and slope aspect. The analysis was conducted by giving weights based on the comparison of soil movement events to the class of each parameter using the Weight of Evidence method. Based on the Weight of Evidence method, the mass movement vulnerability zone is divided into five zones, very low vulnerability zone occupies 7.75%, low vulnerability zone occupies 27.11%, medium vulnerability zone occupies 31.76%, high vulnerability zone occupies 21.72%, and very high vulnerability zone occupies 11.66% of the total study area. Based on validation using the AUC value, the Weight of Evidence Method has a value of 0.771 (Fairly Good Model).